Non-Interference Principle of Asean in The Rohingya Crisis: International Human Rights Law as Alternative Foothold - Oktavian, Alif; Jamaludin, Maun; Hossain, Mohammad Belayet (Intermestic: Journal of International Studies; Vol 7 No 2 (2023), 2023)
This article  evaluates  the  non-interference  principle  of  Association  of  Southeast  Asian  Nations (ASEAN) in resolving the Rohingya crisis. The study emphasized the essential ethical and integrity standards  found  in  international  human  rights  law.  In  this  study, literature  review  is  employed  to gather  data  from  relevant  scientific  sources  by  utilizing  descriptive  qualitative  research  methods. Based  on  theoretical  frameworks  of  human  rights  accountability  with  international  human  rights law in international relations context, the findings highlighted that ASEAN should act in conformity with  international  human  rights  under  the  rules  of  ethics  and  integrity  in  managing  the  regional crisis.  The  findings  assert  the  necessity  of  comparing  a  better  framework  of  international  human rights  to  address  regional  problems  like  the Rohingya  crisis,  as  well  as  any  concerns  that  may develop in the future. As a practical suggestion, a conflict management body needs to be established within ASEAN.